2022
DOI: 10.1021/acsanm.2c03203
|View full text |Cite
|
Sign up to set email alerts
|

Five-Membered Loop-Initiated Nucleation of Unlayered Graphene Sheets in a Carbon Melt, with Diffusion Barrier Possibilities

Abstract: A subset of isotopically “presolar” carbon particles extracted from the Murchison meteorite contain signatures expected of particles formed in the atmosphere of red giant stars. Some of these micron-size particles have spherical cores that show diffraction rings from atom-thick graphene, possibly formed by solidification of liquid carbon at low pressure. Electron phase-contrast transmission electron microscopy (TEM) images suggest that these cores originate from supercooled carbon droplets that formed graphene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 33 publications
2
8
0
Order By: Relevance
“…Independent semiempirical modeling also saw a high preference of carbyne chains for containerless liquid carbon . Another DFT study of liquid carbon at low pressures also noticed a preference for pent-first vs hex-first loop formation during nucleation …”
Section: Introductionmentioning
confidence: 92%
See 4 more Smart Citations
“…Independent semiempirical modeling also saw a high preference of carbyne chains for containerless liquid carbon . Another DFT study of liquid carbon at low pressures also noticed a preference for pent-first vs hex-first loop formation during nucleation …”
Section: Introductionmentioning
confidence: 92%
“…Independent DFT studies have shown that setting b = 5 is likely a more plausible value as low-pressure carbon melts tend toward a "pentagon first mechanism". 10,44 The value for b can also change when considering other factors which affect growth such as edge curvature and shape changes.…”
Section: ■ Analytical and Numerical Modelsmentioning
confidence: 99%
See 3 more Smart Citations